2008
DOI: 10.1016/j.compenvurbsys.2008.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Agent-based services for the validation and calibration of multi-agent models

Abstract: Agent-Based Services for the Validation and Calibration of Multi-Agent ModelsYang Li, Allan Brimicombe, Chao Li Abstract Agent-based modelling in the form of multi-agent models has been increasingly applied to the simulation of spatial phenomena in silico. Validation and calibration are recurrent problems. The complexity of these models with large numbers of parameters can make validation procedures intractable. In this paper, the novel concept of using agent-based technologies to create services that assist i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Consequently, only verification of correct model construction and validation by comparing the results with real data will be discussed further. Verification (also known as internal validation) refers to the correctness of the internal structure, ensuring that the model has been developed in a formally correct manner (e.g., system diagrams, units of measurement, and equations) in accordance with a specified methodology [58]. This implies corroborating that the implemented model conforms to the specifications by running it after changing some initial parameters, as done by other modelers [33].…”
Section: Urban Planner Submodelmentioning
confidence: 96%
See 1 more Smart Citation
“…Consequently, only verification of correct model construction and validation by comparing the results with real data will be discussed further. Verification (also known as internal validation) refers to the correctness of the internal structure, ensuring that the model has been developed in a formally correct manner (e.g., system diagrams, units of measurement, and equations) in accordance with a specified methodology [58]. This implies corroborating that the implemented model conforms to the specifications by running it after changing some initial parameters, as done by other modelers [33].…”
Section: Urban Planner Submodelmentioning
confidence: 96%
“…Several authors have suggested that the validation process should consist of different components: verification, validation, and a sensitivity analysis [12,[53][54][55][56][57][58]. However, since this paper presents a prototype of an ABM, it focuses less on predicting the future and more on understanding and exploring the behavior of the urban system and reproducing specific scenarios.…”
Section: Urban Planner Submodelmentioning
confidence: 99%
“…One of the most important aspects in developing a simulation model is its credibility; hence, the validation and verification of any simulation model is necessary. Multi-agent models are difficult to validate because these models represent a new approach to simulation for which traditional validation methods are not always applicable [12]. Given these challenges, it is essential to know what an appropriate validation process is for such models.…”
Section: Verification and Validation Of Mcdaa Simulation Modelmentioning
confidence: 99%
“…Agent based modeling (ABM) is a simulation paradigm which has close ties with actual scientific experiments thus making it a good technique for evaluation different paradigms (Li, Brimicombe, & Li, 2008). What makes ABM unique for modeling complex adaptive systems is the way an ABM is typically designed.…”
Section: Agent-based Modelingmentioning
confidence: 99%